2000
DOI: 10.1021/bi992725p
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Cytosolic Phospholipase A2 in a New Perspective:  Recruitment of Active Monomers from an Inactive Clustered Pool

Abstract: cPLA 2 plays a key role in many signal transduction cascades by hydrolyzing arachidonic acid from membrane phospholipids. Tight control of cPLA 2 activity by a number of regulatory mechanisms is essential to its cellular function. We recently described the localization of cPLA 2 in clusters in fibroblasts and now propose that these clusters reflect a localized inactive pool from which active monomers can be recruited to keep cPLA 2 activity under control on the subcellular level. Using an electron microscopic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…6A), whereas in NPC2-null cells cPLA2 displayed a reticular/punctate cytoplasmic staining pattern (Fig. 6B) that was reported earlier for both unstimulated and stimulated fibroblasts (43,44). These fluorescence microscopy data correlated well with those of Western blot analysis (Fig.…”
Section: Robust and Selective Up-regulation Of Pge2 Biosynthesis In Nsupporting
confidence: 88%
See 3 more Smart Citations
“…6A), whereas in NPC2-null cells cPLA2 displayed a reticular/punctate cytoplasmic staining pattern (Fig. 6B) that was reported earlier for both unstimulated and stimulated fibroblasts (43,44). These fluorescence microscopy data correlated well with those of Western blot analysis (Fig.…”
Section: Robust and Selective Up-regulation Of Pge2 Biosynthesis In Nsupporting
confidence: 88%
“…cPLA2 is now considered to be a central enzyme in mediating AA release for eicosanoid production, including PGE2 (48,49). The most likely mechanism for constitutive cPLA2 activation and subsequent PGE2 production could include, in addition to its Ser-505 phosphorylation, the release of active cPLA2 monomers from inactive intracellular clusters (43,44). Indeed, it has been previously reported that in fibroblasts, cPLA2 is present in small clusters that were identified as punctuate structures by immunofluorescence and immunogold electron microscopy (43).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…cPLA 2 in Her14 fibroblasts was reported to be localized in clusters near the vicinity of all organellar membranes except for the Golgi apparatus and the nucleus (63). Subsequently, it was shown that these clusters represent the inactive form of cPLA 2 from which active monomers can be recruited that might occur via phosphorylation by p42/44 MAPK (64). Also, p42/44 MAPK phosphorylation has been reported to occur at different locations induced by different agonists.…”
Section: Differential Activation Of P42/44mentioning
confidence: 99%